Design and experimental implementation of a PID-IMC Controller for a VCRS - Carrasco L. (2020)
This paper presents a methodology for the design and the implementation of a PID (Proportional-Integral-Derivative) using IMC (Internal Model Control) tuning method by means of experiments performed on organic banana. In this work, the parameters of the linear and nonlinear model of a cooling chamber for fruits are identified. Simulation studies and implementation of the PID-IMC closed-loop control system demonstrate that energy saving were obtained of the order of 20% with respect to the entire system. © 2020 IEEE.